Emotional intelligence moderated the mediating effect of professional identity between social support and psychological well-being among pre-service teachers - Qi Hui; Yuan Li; Rongjuan Zhu; Ying Li; Tong Wang; Xiang Che; Xuqun You (Scientific Reports)
Abstract Based on the Conservation of Resources Theory, the research explored the relationships between social support and the psychological well-being of pre-service teachers. It specifically examined the mediating effects of professional identity and the moderating impact of emotional intelligence. A cross-sectional survey was conducted using the Perceived Social Support Questionnaire, Teachers’ Professional Identity Scale, Emotional Intelligence Scale, and Flourishing Scale with a sample of 457 (68.10% were female, and 31.90% were male) pre-service teachers in Shaanxi. The results showed that (1) social support of pre-service teachers had a positive and direct effect on psychological well-being; (2) professional identity mediated the positive association between social support and psychological well-being; (3) emotional intelligence moderated the first-stage path of the indirect effect through professional identity. These findings elucidate the role of external resources (social support) and internal resources (professional identity and emotional intelligence) in pre-service teachers, and suggest that comprehensive and holistic intervention programs may be enhancing psychological well-being among pre-service teachers.